Discoidin domain receptor 1 regulates ErbB2/ErbB3 signaling in mammary epithelial cells - Toscani, Andrés Martin (2022)
The ErbB2 receptor tyrosine kinase plays a key role in mammary gland development. It forms large clusters which serve as signaling platforms for integration of extracellular information. The discoidin domain receptor (DDR) family are collagen receptor tyrosine kinases which, together with ErbB2, are involved in many physiological and pathological processes. Here, we investigated the interaction of ErbB2 and DDR1 receptors in breast cancer cells. In contrast to beta1-integrin, DDR1 colocalizes with ErbB2 in membrane clusters regardless of their expression levels. We demonstrated that this spatial coexistence is a consequence of the physical interaction between these receptors. In addition, these receptors are coexpressed in the normal mammary gland but not in breast tumor samples. Together, these results present DDR1 as a novel modulator of the ErbB2/ErbB3 signaling pathway.